The Nigeria Watch Project and the Challenges in the Study of Lethal Violence in Nigeria - (:unkn) unknown (My University, 2021)
Focusing on the Nigeria Watch project (accessible on http://www.nigeriawatch.org/), this article ponders the study of lethal violence in Nigeria and its challenges. Rumors about violent deaths spread widely in Nigeria, most notably through social media. Academics, journalists or members of the public interested in investigating violent phenomena in the country often struggle to find reliable sources. That is why a team of academics decided to set up the Nigeria Watch Project in June 2006. This article examines and discusses the Nigeria Watch Project and its attempt to further the study of violence in Nigeria. Building on several Nigerian newspapers, Nigeria Watch aims at constituting a database of violent deaths on a daily basis. Deadly incidents are coded in the database along with specific information such as causes of death and location. The data is made available for mapping, understanding and analyzing violent trends in Nigeria. The project guarantees open access to its newspaper sources and a set of basic functionalities. More advanced features are available to password holders, who can use the data to create their own visuals, including graphs, charts and maps. This article also recognizes some limits and shortcomings of the database and, more generally, the difficulties of conducting qualitative and quantitative research on violence in African contexts. For instance, sources are a major point of contention: the database relies on newspaper reporting, which is biased and patchy. Categorizing deadly events results also from subjective choices and can be subjected to criticisms. Despite these challenges, the collected data may eventually contribute decisively to identifying patterns of violence in Nigeria, debunking popular misconceptions or myths and informing evidence-based policies.
Keywords: African Research